2021
DOI: 10.1016/j.ynstr.2021.100408
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of the depressed and PTSD brain

Abstract: Stress is the response of an organism to demands for change, yet excessive or chronic stress contributes to nearly all psychiatric disorders. The advent of high-throughput transcriptomic methods such as single cell RNA sequencing poses new opportunities to understand the neurobiology of stress, yet substantial barriers to understanding stress remain. Stress adaptation is an organismal survival mechanism conserved across all organisms, yet there is an infinity of potential stressful experiences. Unraveling shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 139 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…Consistent with our findings, bulk-tissue 9 and single-nucleus 20 RNA-seq in the DLPFC revealed downregulation of genes associated with inflammatory cytokines, microglia– activation, and immune-signaling pathways in MDD. Some studies in rodents 84,90 and humans 91 have likewise suggested suppression of microglial immune-response in chronic stress-induced disorders. Furthermore, recent reports provide evidence at gene-expression 9,10,20,75 and protein levels 10,88,92 for a non-inflammatory microglial phenotype in MDD.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with our findings, bulk-tissue 9 and single-nucleus 20 RNA-seq in the DLPFC revealed downregulation of genes associated with inflammatory cytokines, microglia– activation, and immune-signaling pathways in MDD. Some studies in rodents 84,90 and humans 91 have likewise suggested suppression of microglial immune-response in chronic stress-induced disorders. Furthermore, recent reports provide evidence at gene-expression 9,10,20,75 and protein levels 10,88,92 for a non-inflammatory microglial phenotype in MDD.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, while immunofluorescence of epigenetic markers is more often used to draw preliminary conclusions about changes in transcriptional processes (Chouliaras et al, 2013, Demyanenko andUzdensky, 2019), it is not possible to draw a one-to-one relationship between the observed differences in HDAC2, 5mC and 5hmC levels and actual alterations in histone acetylation and gene expression. Different studies have shown transcriptional alterations in response to stress (Floriou-Servou et al, 2018), and in PTSD specifically , Zhang et al, 2021, but it would require future studies to causally link such changes to the alterations in histone acetylation, DNA methylation and hydroxymethylation that have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…The study was concordant with Girgenti et al who performed a transcriptome-wide analysis on 4 dorsal PFC subregions (including the dlPFC) of individuals with PTSD ( Girgenti et al, 2021 ). Zhang et al (2021) emphasized in their review, both PTSD and MDD have a GABAergic interneuron transcriptional dysregulation; however, PTSD and MDD share few DEGs, suggesting that the dysregulation occurs in different subpopulations of GABAergic interneurons. These results reflect the heterogeneity in cell population and cell function in the brain and suggest that future transcriptomic wide studies using droplet-based single cell genomics to study RNA expression at the single cell and/or single nucleus level would be beneficial.…”
Section: Brain Molecular Studies Of Stress-related Disordersmentioning
confidence: 99%